2017
DOI: 10.1002/ecy.1853
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of a species’ response to press perturbations with high food web uncertainty

Abstract: Predicting species responses to perturbations is a fundamental challenge in ecology. Decision makers must often identify management perturbations that are the most likely to deliver a desirable management outcome despite incomplete information on the pattern and strength of food web links. Motivated by a current fishery decline in inland lakes of the Midwestern United States, we evaluate consistency of the responses of a target species (walleye [Sander vitreus]) to press perturbations. We represented food web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…At the very least, our analysis suggests that it is possible, for dynamic models calibrated to time‐series data, to provide useful predictions for decision‐making. More generally, approaches such as ours that formally account for uncertainty propagation are advantageous because they can predict the probability of an undesirable outcome (Regan et al ; Tunney et al ). Our results therefore support the view that we do not need to wait until ecological models are well‐constrained in their predictions before we start forecasting (Houlahan et al ; Dietze et al ); even a model that is not particularly well‐constrained in its predictions can potentially be used for management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…At the very least, our analysis suggests that it is possible, for dynamic models calibrated to time‐series data, to provide useful predictions for decision‐making. More generally, approaches such as ours that formally account for uncertainty propagation are advantageous because they can predict the probability of an undesirable outcome (Regan et al ; Tunney et al ). Our results therefore support the view that we do not need to wait until ecological models are well‐constrained in their predictions before we start forecasting (Houlahan et al ; Dietze et al ); even a model that is not particularly well‐constrained in its predictions can potentially be used for management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study (and many previous studies, Montoya et al, 2009;Pires et al, 2020) comes from the assumption of a Holling type I (linear) functional response. Although previous studies demonstrated that net effects assuming a linear functional form could be a useful way of predicting outcomes of press perturbation (Schmitz, 1997;Tunney et al, 2017), nonlinear functional forms (Holling type II or III) can theoretically alter the direct interaction effects and consequently net effects (Novak et al, 2016) if inverse matrix approach is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the existing relevant studies are restricted to very few systems. Nonetheless, several pioneering studies have shown that the outcomes of press perturbation might be closely linked to both the topologies and indirect interactions of ecological networks (Novak et al, 2011;Tunney et al, 2017). For example, when a press disturbance affects a generalist, it was found that this is unlikely to have a major effect on the population biomass of the remaining species in the food web if indirect effects are taken into account (Montoya et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Largemouth bass populations are now essentially unmanaged in Northern Wisconsin because the primary tool of management—harvest regulation—is not impacting bass populations. It is possible that largemouth bass are important competitors or predators of young‐of‐year walleye and thereby are playing a role in the walleye decline (Hansen et al 2015 c , Tunney et al 2017), although examination of largemouth bass diets does not support this hypothesis (Kelling et al 2016).…”
Section: Eroding Resilience Of Northern Wisconsin Cool‐water Fisheries: Climate and Habitatmentioning
confidence: 99%
“…Largemouth bass populations are now essentially unmanaged in Northern Wisconsin because the primary tool of management-harvest regulation-is not impacting bass populations. It is possible that largemouth bass are important competitors or predators of young-ofyear walleye and thereby are playing a role in the walleye decline (Hansen et al 2015c, Tunney et al 2017, although examination of largemouth Climate warming may play a role in both declining walleye and increasing largemouth bass populations in northern Wisconsin lakes. To test this hypothesis, coupled physical and fish population models were developed and calibrated for 2148 Northern Wisconsin lakes, including NTL LTER study lakes, under contemporary climate and then applied to future (2040-2089) climate projections (Hansen et al 2017).…”
Section: Eroding Resilience Of Northern Wisconsin Cool-water Fisheries: Climate and Habitatmentioning
confidence: 99%